Media Literacy in Information Chaos Era: Qualitative Study Bandung Literacy Activist - Cevi Mochamad Taufik; Suhaeri Suhaeri (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2020)
Media must get control in order that the practice is not authoritative. In the context, when it is in an individualist form, it tends to produce information without considering the norm. In the individualist characteristic, all the information flow spread massively with the tendency for thick interest. The research arranged to find out literacy activities in this chaotic era, using qualitative descriptive methods to uncover the minds of literacy avtivists in the information chaos era. The aim is to find out the form of literacy in accordance with the chaotic conditions of information and literacy activities in growing public awareness in information management. The results showed that literacy forms carried out through the introduction of media (media knowledge) concerning the credibility of the media and recognizing the nature of mainstream and non-mainstream media. Another platform is digital literacy and management of public information. Meanwhile, to raise public awareness is done by producing digital content in anticipation of hoax news, making fact check content, media practices through radio broadcasts and websites, introduction to news construction.